Willingness of Medical Students to Participate in the Response to Covid-19 Pandemic in Sudan, 2020 - Elsheikh, Ethar Hajo Ahmed; Saeed, Esra Ali Mahjoub; Saleh, Ghaida Ahmed Hamed; Gadeltayeb, Fatimah Azhari Gasmalla; MaliK, Elfatih M (Archives of Clinical and Biomedical Research, 2020)
Introduction: Coronavirus disease 2019 is a pandemic crisis affecting all aspects of life. The health workers are making effort to decrease the impact of this disease on people. But With the increasing number of cases throughout the world there should be an equal response to ease this threat. For that our study aims to assess the willingness of medical students to be involved in COVID-19 management. Methods: Institutional based cross-sectional study was conducted at 12 medical schools in Sudan, randomly selected by cluster sampling method and, from each, 60 students were conveniently chosen to fill the self- administered online questionnaire. The information collected contained demographic data, knowledge, attitude and practice toward Covid-19, source of information and willingness to participate. Ethical clearance was obtained from University of Khartoum Community Medicine department. Results: A total of 198 male and 424 female students has participated in this study. 74.4% of the students mentioned that their main source of information was social media including study groups. The majority (81.4%) of the students were willing to participate in COVID-19 response efforts while the main cause of refusal was to avoid getting infected. There is significant association between willingness of medical students to participate to contain COVID-19 and state of residence and the overall score of attitude. Conclusion: Most of the students were willing to participate in COVID-19 management and most commonly in health education/awareness raising. Medical faculties and Ministry of Health should make use of medical student and involving them in the efforts to contain COVID-19.